Morphology and germination of Acmella oleracea L. R. Jansen under different temperatures and photoperiods - Sarmento, Erivanessa; Pereira, Kleane Targino; Oliveira, Fernando; Leal, Caio César; Torres, Salvador; Dutra, Alek (Revista Ciência Agronômica, 2019)
The objective was to evaluate the physical characteristics and physiological behavior of A. oleracea seeds during imbibition and germination, under different temperatures and photoperiods, as well as to determine the duration of the germination test. For this, biometric parameters (length, width and thickness) were measured in 100 seeds and thousand-seed weight was determined. In addition, the external structures of seeds and seedlings were described and the imbibition curve was monitored. Subsequently, the germination test was conducted at temperatures of 20, 25, 30, 35, 20-30 and 25-35 ºC, under constant and alternating light and dark photoperiods (12 h), arranged in 6 x 3 factorial scheme, with four replicates of 50 seeds. Seeds were sown in transparent plastic boxes with blotting paper as substrate, germinated in Biochemical Oxygen Demand (B.O.D) incubator, and evaluated for six days. The following variables were analyzed: germination, germination speed index, seedling length and seedling dry mass. The imbibition pattern test was conducted at 25 ºC with 4 replicates of 100 seeds, evaluated until 50% root protrusion occurred. A. oleracea seeds exhibit uniform physical characteristics and the three-phase model as a water absorption pattern. Constant temperatures of 25 and 30 °C and alternating temperatures of 20-30 °C, regardless of the photoperiod, led to higher germination values. For A. oleracea, the germination test evaluations can be performed on the fourth and sixth day after sowing, as first and last counts, respectively.